2021
DOI: 10.1002/pits.22608
|View full text |Cite
|
Sign up to set email alerts
|

The association between teacher‐student relationship and academic achievement: The moderating effect of parental involvement

Abstract: As an important part of adolescents' social capital, teacherstudent relationship (TSR) and parental involvement (PI) are important for student learning. However, we know little about how PI works with TSR in relation to adolescents' learning

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 58 publications
(158 reference statements)
0
16
0
Order By: Relevance
“…It is thus suggested that the sample frame should be increased, and the parental engagement should be measured through direct responses of the parents rather than students' perceived parental engagement. The finding on the non-moderating influence of parental engagement is discordant with (Ma et al, 2022) that parental involvement moderated the relationship between teacher-students relationship (TSR) and students' academic achievement.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…It is thus suggested that the sample frame should be increased, and the parental engagement should be measured through direct responses of the parents rather than students' perceived parental engagement. The finding on the non-moderating influence of parental engagement is discordant with (Ma et al, 2022) that parental involvement moderated the relationship between teacher-students relationship (TSR) and students' academic achievement.…”
Section: Discussionmentioning
confidence: 71%
“…This finding is similar to that of the mixed-method study of (Black, 2022) which revealed that parents and students agreed that parental involvement could tremendously boost students' academic achievement because learners feel more comfortable asking questions and getting answers from more knowledgeable adults. Ma, Liu, & Li (2022) studied the association between a teacher-student relationship (TSR) and adolescent learning outcomes in China (Ma et al, 2022). They also tested the potency of parental involvement (PI) in moderating the relationship.…”
Section: Pedagogi: Jurnal Ilmu Pendidikanmentioning
confidence: 99%
“…Secondly, we investigated how different types of conflict are associated with students' creativity. In contrast with previous studies, which have primarily focused on the detrimental consequences of conflict [10,49,51], this research provided empirical evidence regarding the positive outcomes of two types of teacher-student conflict in the classroom (understanding conflict and process conflict).…”
Section: Discussionmentioning
confidence: 85%
“…However, because critical thinking was highlighted in students' creativity, conflict should not always be considered as a disruptive factor in the regular class process. Many teachers are unaware of the potential for conflict, seek to prohibit it, or deal with it irrationally [43,51]. A more effective teacher is able not only to convey knowledge but is also dedicated to inspiring students' creativity.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have also focused on the analysis of how a teacher-student relationship affects students' achievement and vice versa-how students' achievement influence relationships between teacher and student. A study by Ma, Liu, and Li [28] in mainland China adolescents shows that there is a positive correlation between a teacher-student relationship and students' academic performance. Lee's [29] investigation revealed that the teacher-student relationship was a meaningful predictor on students reading performance.…”
Section: Theoretical Backgroundmentioning
confidence: 99%